2020
DOI: 10.1128/mcb.00212-19
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic SIRT4 Exerts Retrograde Control over TORC1 Signaling by Glutamine Sparing in the Mitochondria

Abstract: Anabolic and catabolic signaling mediated via mTOR and AMPK (AMP-activated kinase) have to be intrinsically coupled to mitochondrial functions for maintaining homeostasis and mitigate cellular/organismal stress. Although glutamine is known to activate mTOR, whether and how differential mitochondrial utilization of glutamine impinges on mTOR signaling has been less explored. Mitochondrial SIRT4, which unlike other sirtuins is induced in a fed state, is known to inhibit catabolic signaling/pathways through the A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…The circulating concentration of AKG, which decreases with ageing [ 8 ] but increases upon fasting [ 9 ], hypoxia [ 11 ] and exercise [ 10 , 44 ], reflects changes in metabolic flux. Interestingly, the changes in circulating AKG levels reported in previous studies on HF metabolites are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circulating concentration of AKG, which decreases with ageing [ 8 ] but increases upon fasting [ 9 ], hypoxia [ 11 ] and exercise [ 10 , 44 ], reflects changes in metabolic flux. Interestingly, the changes in circulating AKG levels reported in previous studies on HF metabolites are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…AKG (α-KG), also known as 2-oxoglutarate (2-OG), is an important intermediate in the TCA cycle between succinyl-CoA and isocitrate and regulates adenosine triphosphate (ATP) production as a crucial point in the anaplerotic reaction [ 7 ]. The circulating AKG concentration was found to decrease with ageing [ 8 ] and is elevated under fasted states [ 9 ], after acute exercise [ 10 ] and resistance exercise [ 11 ], and in HF [ 5 , 6 ]. Clinical studies showed that a high circulating AKG level was associated with HF severity (NYHA classification) and adverse outcome in acute HF (AHF) and chronic HF (AHF) patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our work is the first to observe increased gdh transcript levels associated with the presence of Wolbachia infection. This Such correlation coupled with (1) the predicted presence of amino acid uptake transporters and their associated metabolic pathways (glutamine included) in the genome of distinct Wolbachia strains [ 23 , 24 ], and (2) the observation that SIRT-4 (known to directly inhibit GDH activity) protein levels peak in a nutrient rich environment [ 69 ], together suggests that Wolbachia might be acting as a nutrient scavenger, depleting the host of key nutrients. This depletion might then mimic a calorie restriction scenario driving the downregulation of host sirt-4 , and leading to upregulation of its direct target gdh in order to compensate for such energetic loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that yeast-enriched diet resulted in reduced ovarian Wolbachia titer via TORC1, in which the upstream effectors remain to be discovered [ 42 ]. Additionally, exciting recent work has shown that GDH inhibition via SIRT-4 leads to mTORC1 activation [ 69 ]. As such, by linking previous work to our data presented here, we propose that the observed reduction in Wolbachia density detected in flies reared on a yeast-enriched diet is potentially the result of the upstream effector SIRT-4.…”
Section: Discussionmentioning
confidence: 99%
“…Others and we have found that metabolic cues under fasting conditions elicit anticipatory molecular mechanisms to mount an efficient fed response ( 49 51 ). In this context, we have unraveled that pulsatile 0.1 nM insulin rewires signaling dynamics in response to 1 nM inputs.…”
Section: Discussionmentioning
confidence: 82%